Erythropoietin improves neurobehavior by reducing dopaminergic neuron loss in a 6-hydroxydopamine-induced rat model - QI, CHEN (D.A. Spandidos, 2014)
The purpose of this study was to determine the effectiveness of the systemic administration of high dose erythropoietin (EPO) in a 6-hydroxydopamine (6-OHDA)- induced rat model. Rats were divided into 7 groups. Groups 1–4 were administered daily EPO doses of 0; 2,500; 5,000 and 10,000 U/kg via intraperitoneal injection (i.p.) for 5 days. The EPO concentration in cerebrospinal fluid (CSF) was determined by enzyme-linked immunosorbent assay (ELISA) and western blot analysis. The dose of 10,000 U/kg was then selected for subsequent experiments. In group 5, rats received saline via medial forebrain bundle (MFB). In group 6, rats received 6-OHDA via MFB. In group 7, an EPO concentration of 10,000 U/kg was constantly administered i.p. for 5 days to rats prior to 6-OHDA injection via MFB. Behavioral analysis was performed for groups 5–7 by rat rotation tests. The number of tyrosine hydroxylase (TH)-immunopositive cells in the substantia nigra (SN) was measured by immunocytochemistry. The activation of c-Jun N-terminal kinase (JNK), extracellular signal-regulated kinase (ERK), p38 mitogen-activated protein kinases (MAPKs) and caspase-3 signaling in rats were analyzed using western blotting. The results showed that there was a significant increase in EPO levels in the CSF in 10,000 U/kg group compared with the 2,500 and 5,000 U/kg groups (P<0.01). Significantly fewer rotational counts were obtained in rats that were pretreated with EPO compared with saline-pretreated 6-OHDA-lesioned rats (P<0.001). The dopaminergic neurons in the 6-OHDA-lesioned SN were also increased in the EPO-pretreated rats when compared with control rats (P<0.01). Western blot analysis revealed that EPO inhibited the 6-OHDA-induced activation of JNK, ERK, p38 MAPK and caspase-3 signaling in the rat model. In conclusion, systemic administration of a high dose of EPO exerted neuroprotective effects in reversing behavioral deficits associated with Parkinson’s disease and prevented loss of the dopaminergic neurons through the MAPK pathway.